The Shadow of Islamic Ortodoxy and Syncretism in Contemporary Indonesian - Ahmad Khoirul Umam; Akhmad Arif Junaidi (Al-Ulum, 2011)
The mapping of political affiliation is important to capture the power direction and its characteristics in the future. Generally, the mass political orientation in Indonesia is not much different than what was outlined by Clifford Geertz in his master piece entitled The Religion of Java. The concept of 'trikotomi' consisting of the Santri, Abangan, and Priyayi, which over the past five decades has been the fundamentally critiqued by various parties. Numerous weak points and fallacy of conceptual framwork then become the entrance to reconceptualize the Indonesian people political orientation. However, the work of Geertz's initial approach should be appreciated as a brilliant in understanding the Indonesian political behavior. With the critical approaches, the Geertz's approaches will again be utilized to mapthe direction of community in the contemporary Indonesian political orientation.